2011
DOI: 10.14238/pi51.3.2011.163-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment of children with thalassemia

Abstract: Background Thalassemia is a chronic disease that is becoming a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 1 publication
(2 reference statements)
1
18
1
7
Order By: Relevance
“…this reflect the poverty and bad health status of the patient which prevent them to continue graduation to high level of education, also because the complications of disease are increase with increasing age and they need follow up to thalassemic center for treatment and lead to frequent absence from school. This is similar to Wahyuni, M. S. et al 2011 [20] result in which they found that most of the participants in their study were of primary level of education.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…this reflect the poverty and bad health status of the patient which prevent them to continue graduation to high level of education, also because the complications of disease are increase with increasing age and they need follow up to thalassemic center for treatment and lead to frequent absence from school. This is similar to Wahyuni, M. S. et al 2011 [20] result in which they found that most of the participants in their study were of primary level of education.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 89%
“…[20] who studied the health related quality of life in thalassemia treated with iron chelation, they found that the majority of the study subjects were with regular chelation therapy (75.29%).…”
Section: Medical Historymentioning
confidence: 99%
“…In a case-control study, Wahyuni and colleagues compared QoL of children with β-thalassemia major with their normal siblings (Wahyuni et al, 2011). They reported that QoL of children with β-thalassemia major is significantly lower than their normal siblings (Wahyuni et al, 2011). In another study, Ayoub investigated QoL among children with β-thalassemia major in Western Saudi Arabia with similar results.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, thalassemia has been spread across Iran, more prevalent in some provinces including Gillan, Mazandaran, Golestan, Bushehr, Hormozgan, Sistan-o-Baluchestan, Khuzestan, Fars and South of Kerman provinces (Gh & Ghaderi, 2013). Wahyuni et al, 2011). In a case-control study, Wahyuni and colleagues compared QoL of children with β-thalassemia major with their normal siblings (Wahyuni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation